Studi Komparasi Kurikulum Bahasa Arab Tingkat Satuan Pendidikan dan Kurikulum 2013 Satuan Pendidikan dan Kurikulum 2013 - Nurul Aini (al Mahāra: Jurnal Pendidikan Bahasa Arab, 2015)
This paper aims to find out the similarities and differences contained in the KTSP and the 2013 curriculum Arabic subjects Madrasah Aliyah from the aspect of goals, materials, and methods. As well as knowing the advantages and disadvantages of both curriculum. Types of research this is library research with a qualitative approach. Analysis of the data uses content analysis. Based on analysis concluded that in the KTSP and the 2013 Arabic Curriculum for Madrasah Aliyah, it has many similarities in aspects of purpose, material or method. It's just that the 2013 curriculum tries to complement its deficiencies in KTSP as in the subject matter, the 2013 curriculum is more detailed in describing the scope of the material in the form of KI and KD, besides that the 2013 curriculum does not only emphasize cognitive aspects only, but cognitive, psychomotor and affective aspects balanced and integrated into all subjects. Addition to that, if in the KTSP the learning approach used varies, then the 2013 curriculum uses a scientific approach.